Faktor-Faktor Yang Mempengaruhi Keputusan Nasabah Untuk Menggunakan Jasa Perbankan Syariah Di Kota Tasikmalaya - D. Desiana; Dewi Susilowati; Negina Kencono Putri (Department of Accounting-Faculty of Economic and Business (FEB), 2018)
This study aims to analyze the factors that influence the customers’ decision in using Islamic banking in Tasikmalaya. This study uses a quantitative method. The data used in this study is primary data. Primary data was obtained from questionnaires distributed to a hundred customers of Islamic banking in Tasikmalaya. Analysis of data uses multiple linear regression and the results show that in partial the variable of profit sharing has significantly positive effect on the customers' decision to use islamic banking, the variable of religion quality has significantly positive effect on the customer’s decision to use islamic banking, the variable of education has significantly positive effect on the customer's decision to use islamic banking,the variable of income doesn’t have significantly positive effect on the customer’s decision to use islamic banking and the variable of products and services have significantly positive effect on the customers’ decision to use islamic banking in Tasikmalaya.